The impact of Mild Behavioral Impairment on the individual's level of psychological, social, and occupational functioning. (1st June 2022) - Elefante, C.; Brancati, G.E.; Gemmellaro, T.; Ricciardulli, S.; Romeo, F.; Torrigiani, S.; Pistolesi, G.; Amadori, S.; Lattanzi, L.; Perugi, G.
Abstract : Introduction: Mild behavioral impairment (MBI) is a neurobehavioral syndrome characterized by later-life emergent neuropsychiatric symptoms, which represent an at-risk state for incident cognitive decline and dementia. Objectives: Our obective was to prospectively evaluate the impact of MBI on global functioning in patients ≥ 50 years with a major depressive episode (MDE) at baseline. Methods: We recruited 51 patients ≥ 50 years presenting with a MDE at the outpatient clinic of the 2 nd Psychiatric Unit of the University of Pisa. Then we selected those patients who had a follow-up of at least two months and excluded subjects with a neurodegenerative disease. The included patients (N = 25) were subdivided in a subgroup with MBI and a subgroup without MBI. The subgroups have been compared for the difference between baseline and follow-up score in global functioning according Global Assessment of Functioning (GAF) scale. Comparative analyses were conducted by means of mixed anova. Results: There was a significant interaction effect between time and the MBI condition (F[1, 23] = 4.12, p = 0.05 η p 2 = 0.15). Descriptive statistics showed that while patients without MBI showed higher GAF score at follow-up (mean = 65.12) compared to GAF score at baseline (mean = 54.37), patients with MBI showed, on average, the same GAF score at follow-up (mean = 54.44) and at baseline (mean = 54.44). Conclusions: In patients with MDE, the presence of MBI is related to a lack of improvement in psychological, social, and occupational functioning in the short-term Disclosure: No significant relationships.